Responses of Intestinal Microbiota and Immunity to Increasing Dietary Levels of Iron Using a Piglet Model - Chen, Shuai; Wu, Xin; Wang, Xia; Shao, Yirui; Tu, Qiang; Yang, Huansheng; Yin, Jie; Yin, Yulong (Frontiers in Cell and Developmental Biology, 2020)
Iron is an essential metal for both animals and microbiota. In general, neonates and infants of humans and animals are at the risk of iron insufficient. However, excess dietary iron usually causes negative impacts on the host and microbiota. This study aimed to investigate over-loaded dietary iron supplementation on growth performance, the distribution pattern of iron in the gut lumen and the host, intestinal microbiota, and intestine transcript profile of piglets. Sixty healthy weaning piglets were randomly assigned to six groups: fed with diets supplemented with ferrous sulfate monohydrate at the dose of 50ppm (Fe50 group), 100ppm (Fe100 group), 200ppm (Fe200 group), 500ppm (Fe500 group), and 800ppm (Fe800) for three weeks. The results indicated that increasing iron had no significant effects on growth performance but increased diarrheal risk and iron deposition in intestinal digesta, tissues of intestine and liver, and serum. High iron also reduced serum iron-binding capacity, apolipoprotein, and immunoglobin A. The RNA-sequencing analysis revealed that iron changed colonic transcript profile, such as interferon gamma-signal transducer and activator of transcription two based anti-infection gene network. Increasing iron also shifted colonic and cecal microbiota, such as reducing alpha diversity and the relative abundance of Clostridiales and Lactobacillus reuteri, and increasing the relative abundance of Lactobacillus and Lactobacillus amylovorus. Collectively, this study demonstrated that high dietary iron increased diarrheal incidence, changed intestinal immune response-associated gene expression, and shifts gut microbiota. The results would enhance our knowledge of iron effects on the gut and microbiome in piglets, and further contribute to understanding these aspects in humans.